Inhibitors of retrograde trafficking active against ricin and Shiga toxins also protect cells from several viruses, Leishmania and Chlamydiales. (1st April 2017) - Gupta, Neetu; Noël, Romain; Goudet, Amélie; Hinsinger, Karen; Michau, Aurélien; Pons, Valérie; Abdelkafi, Hajer; Secher, Thomas; Shima, Ayaka; Shtanko, Olena; Sakurai, Yasuteru; Cojean, Sandrine; et al.
Abstract: Medical countermeasures to treat biothreat agent infections require broad-spectrum therapeutics that do not induce agent resistance. A cell-based high-throughput screen (HTS) against ricin toxin combined with hit optimization allowed selection of a family of compounds that meet these requirements. The hit compound Retro-2 and its derivatives have been demonstrated to be safe in vivo in mice even at high doses. Moreover, Retro-2 is an inhibitor of retrograde transport that affects syntaxin-5-dependent toxins and pathogens. As a consequence, it has a broad-spectrum activity that has been demonstrated both in vitro and in vivo against ricin, Shiga toxin-producing O104:H4 entero-hemorrhagic E. coli and Leishmania sp. and in vitro against Ebola, Marburg and poxviruses and Chlamydiales. An effect is anticipated on other toxins or pathogens that use retrograde trafficking and syntaxin-5. Since Retro-2 targets cell components of the host and not directly the pathogen, no selection of resistant pathogens is expected. These lead compounds need now to be developed as drugs for human use. Highlights: The molecule Retro-2 identified by HTS protects cells from ricin and Shiga toxins. Retro-2 acts by blocking toxin trafficking from early endosomes to the Golgi. Acting on a cellular target, Retro-2 protects cells from many intracellular pathogens. Retro-2 protected mice from ricin, Shiga toxin-producing E. coli and Leishmania . The optimized analogue Retro-2.1 is 1000 fold more active than Retro-2 against ricin.